2018
DOI: 10.1101/316901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Development of Sesamoid Bones

Abstract: Sesamoid bones are a special group of small auxiliary bones that form in proximity to joints and contribute to their stability and function. Sesamoid bones display high degree of variability in size, location, penetrance and anatomical connection to the main skeleton across vertebrate species. Therefore, providing a comprehensive developmental model or classification system for sesamoid bones is challenging. Here, we examine the developmental mechanisms of three anatomically different sesamoid bones, namely pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Consequently, differences among species in the association of the calcar with the calcaneus may be the result of relatively minor developmental alterations. Our finding of many sesamoids in bat feet, consistent with a recent assessment of bat sesamoids (Amador et al 2018), suggests a propensity for metaplastic cartilage and bone development in bat feet, as tendon metaplasia is hypothesized to play a role in sesamoid development (Sarin et al 2002; but see also Eyal et al 2015Eyal et al , 2018.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, differences among species in the association of the calcar with the calcaneus may be the result of relatively minor developmental alterations. Our finding of many sesamoids in bat feet, consistent with a recent assessment of bat sesamoids (Amador et al 2018), suggests a propensity for metaplastic cartilage and bone development in bat feet, as tendon metaplasia is hypothesized to play a role in sesamoid development (Sarin et al 2002; but see also Eyal et al 2015Eyal et al , 2018.…”
Section: Discussionsupporting
confidence: 89%
“…The facultative appearance of sesamoids proposed herein is in line with epigenetic theory of sesamoid origins (Newman & Müller, ). Other authors have suggested that, for example, the patella, the lateral fabella and digit sesamoids could arise without a requirement for mechanical load, which may be necessary only later in development for their maintenance (Eyal et al, , a ; Márquez‐Flóres et al, ). It could be thus posited that sesamoid genesis is initiated by biochemical (genetic) signals, followed by epigenetic mechanical signals to trigger sesamoid posterior growth, conservation, and final tissue composition (see Carter et al, ).…”
Section: Historical Hypotheses On Sesamoid Genesismentioning
confidence: 99%
“…() and Eyal et al . (, a ) contributed cellular and molecular evidence on the development of bone prominences and attachment units, placing both them and sesamoids in one category of cartilage elements developing from the same molecular chondroprogenitors ( Sox9 + / Scx + ). Koyama et al .…”
Section: A Dynamic Model Of the Genesis Of New Skeletal Morphologiesmentioning
confidence: 99%
See 2 more Smart Citations